The Global Assault on Teaching, Teachers, and their Unions
XV, 281 p. 1 illus.
Keywords: Public education's character is increasingly under assault as privatization of education is advanced. This collection of essays by noted scholars, teacher activists, and teacher's union leaders from around the world fuses insights with background and analysis to make real the goal of quality education for all the world's children.